Analysis of the Utilization of Posbindu for Non-Communicable Diseases among the Elderly in the Region Kerja Public Health Center Kuta Krueng District of Pidie Jaya - Sibrina; Aramico, Basri; Azwar, Eddy (International Journal of Applied Research and Sustainable Sciences, 2024)
The Integrated Development Post for Non-Communicable Diseases (Posbindu PTM) is one of the facilities that involves community participation in carrying out early detection and monitoring of NCD risk factors. Quantitative research with a cross-sectional approach. The population of all elderly people in the Kuta Krueng Health Center working area is 581 people. The sample was 85 people. The research results showed that 76.5% did not utilize Posbindu PTM. The research conclusion is that there is a relationship between family support (p-value 0.034), physical condition (p-value 0.016), perceived benefits (p-value 0.000), knowledge (p-value 0.004) and the use of Posbindu PTM. Efforts are needed to increase family support, improve physical condition, perception of benefits, and increase knowledge of elderly people about non-communicable diseases and efforts to prevent them